On the Role of Technology in Political Communication Research - B. Dylko, Ivan (Javnost-The Public, 2013)
This article reviews multi-disciplinary body of research to develop a model of how technology impacts communication processes at various stages. The model, which includes psychological and technological factors, is argued to represent a more useful framework for political communication- effects theory building than frameworks offered by either social constructivist or technological determinism perspectives. The article also argues for a greater inclusion of technology into existing political communication theorising. Several future research directions further developing this argument are described.